Rancang Bangun Aplikasi Petani Sawah Sugita Menggunakan Algoritma Dijkstra Untuk Mempermudah Penjualan Hasil Pertanian - Stephen Aprius Sutresno; Eugenius Kau Suni (Journal of Information System Research (JOSH), 2023)
In general, the buyers of rice field produce are often middlemen who offer the lowest possible prices to the farmers. This is due to the lengthy distribution chain that causes a significant price difference between the low prices paid to farmers for their rice and the high prices consumers pay for milled rice. Therefore, in an effort to cut out the distribution chain that disadvantages both farmers and consumers, the idea of developing the Petani Sawah Sugita mobile-based application emerged. This application enables farmers to sell their rice and milled rice directly to consumers at prices that benefit both parties. The research was conducted by applying the four main stages of the SDLC. The requirements analysis phase involved observations and direct interviews with farmers in one of the rice fields located in the Ciasuk area, Tangerang Regency, Banten. The design phase was carried out by creating UML diagrams. The implementation phase was done with the assistance of Android Studio, resulting in the Sugita Rice Field Farmer mobile application. The application's standout feature is the location search for farmers or nearest products from users, built using the Dijkstra algorithm. The system testing phase was performed using black box testing. The test results showed that 105 out of 114 test cases, or 92.1%, met the expected outcomes. In conclusion, the development of the Sugita Rice Field Farmer application proceeded well and was successfully implemented. This application can help reduce product delivery costs and foster relationships between users and farmers. Furthermore, it simplifies the process for farmers to market their agricultural products to the wider community and provides valuable experience for farmers to stay up-to-date and leverage existing technology advancements.